Valorização da lignina - um panorama geral - Bonatti, Érika (Universidade Federal de São Carlos, 2022)
The urge to reduce greenhouse gas emissions, combined with the severe damage to the environment, such as the increase in the average world’s temperature, lead to incentives for research aimed at sustainable development. Consequently, the discussion about the transition from fossil resources to renewable raw materials and energy has become increasingly popular. Among the possible renewable sources, biomass has been gaining more and more prominence in recent years, due to its abundance and energy potential to replace petroleum derivatives. In particular, lignocellulosic biomass has advantages associated with the non-competition with the food sector, as well as opportunities for economic development and minimization of waste in agricultural areas. For this reason, lignocellulosic biomass has become the target for further studies and research. In this sense, although many advances have been made in terms of the valorization of cellulose and hemicellulose, the valorization of lignin is still a great challenge for researchers, due to its structural complexity and variable composition. The present work aims to highlight the state of the art in terms of fractionation, depolymerization and lignin valorization processes and the main renewable products that can be obtained through the improvement of the current conversion technologies.
Lignin valorization - an overview
Keywords: Biomassa lignocelulósica; Lignina; Valorização da biomassa; Tecnologias de fracionamento; Tecnologias de conversão; Lignocellulosic biomass; Lignin; Biomass valorization; Frationation technologies; Conversion technologies; CIENCIAS EXATAS E DA TERRA::QUIMICA